2012
DOI: 10.1007/s10585-012-9518-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of CXCR4 in human salivary gland cancers

Abstract: Salivary gland cancers (SGCs) frequently metastasize to cervical lymph nodes and distant organs. Currently, the mechanisms responsible for the metastatic behavior of SGC cells are not fully understood. We previously demonstrated that the stromal cell-derived factor-1 (SDF-1; also known as CXCL12)/CXCR4 system is involved in the establishment of metastasis in oral squamous cell carcinoma. In the present study, we investigated the role of CXCR4 in the metastatic behavior of SGCs. We examined the expression of CX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Pretreatment with 30 mg/kg Plerixafor® significantly reduced the tracer uptake in the tumor (SUV 0.65 ± 0.08 vs. 0.20 ± 0.01, p  < 0.05). Figure 1 shows that pretreatment with the CXCR4 antagonist also reduces tracer uptake in the salivary glands, which can be explained by the relatively high expression levels of the CXCR4 receptors in these glands [17].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment with 30 mg/kg Plerixafor® significantly reduced the tracer uptake in the tumor (SUV 0.65 ± 0.08 vs. 0.20 ± 0.01, p  < 0.05). Figure 1 shows that pretreatment with the CXCR4 antagonist also reduces tracer uptake in the salivary glands, which can be explained by the relatively high expression levels of the CXCR4 receptors in these glands [17].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In the common organs affected by metastatic pancreatic cancer, such as the liver and lungs, increased expression of CXCL12 has been demonstrated, suggesting that the CXCL12/CXCR4 axis serves a role in the organ-specific metastasis of cancer cells (28). The results of a previous study demonstrated that cancer cells metastasize along the concentration gradient of CXCL12 in salivary gland carcinoma (29). CXCR4 is essential in this process, and the application of CXCR4 antagonist ADM3100 could interrupt the metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…CXCR4 is essential in this process, and the application of CXCR4 antagonist ADM3100 could interrupt the metastasis of cancer cells. CXCL12/CXCR4 has been revealed to serve an essential role in tumor cell chemotaxis, proliferation, invasion, angiogenesis, and in particular, organ-specific tumor metastasis (29). The overexpression of CXCR4 in tumor cells and the increased expression of CXCL12 in the cells of target organs facilitate tumor metastasis through the CXCL12/CXCR4 axis (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In our broader examination of the transcriptome of angiogenic and nonangiogenic cell types, additional differences in gene expression were observed. Many of the most highly upregulated genes in revertant clones have been previously implicated in tumor progression and/or metastasis (3543) This might suggest that upregulation of these genes in revertant clones is a secondary effect of the overall decrease in angiogenesis induced by these cells and that the primary determinants of the reduced angiogenic stimulus remain to be determined. Pathway and gene ontological analysis of differentially expressed genes in angiogenic and revertant clones highlighted a number of possible mechanisms for the differential ability of these cells to stimulate tumor growth beyond a particular size.…”
Section: Discussionmentioning
confidence: 99%